أثر سلسلة التوريد على الأداء دراسة حالة مؤسسة مطاحن الحضنة بالمسيلة - ملياني, نور الدين (جامعة المسيلة, 2018)
The study aimed at clarifying the impact of the supply chain in its various dimensions in improving the performance of the incubator mills. To achieve this objective, the questionnaire was used as a data collection tool. The questionnaire was distributed to a sample of 47 managers. Between the supply chain with its dimensions in the study and improving the performance of the incubator mills company. After the network preparation of the most influential supply systems in performance improvement came after the development of the supply chain and finally after the customer division.
Keywords: Supply Chain, Supply Chain, Performance.